ENCORE! Getting to the core of the ischemic core at the core lab - Liebeskind, David S.; Brown, Scott; Yoo, Albert J. (Frontiers in Stroke, 2024)
The recent results of large core trials in acute ischemic stroke prompt the most influential paradigm shift in over a decade since endovascular therapy (EVT) was proven as the mainstay of acute stroke treatment. Six randomized, controlled trials (RCTs) of EVT in patients with more extensive ischemia on imaging than prior approved treatment indications revealed a consistent benefit of EVT, despite different imaging criteria and ischemic core definitions across the individual trials. These findings unfolded sequentially, akin to the acts of a drama, with the story evolving until perhaps the most conclusive results on extensive ischemia treatment about to be published. At this juncture, it is important to summarize the collective findings of these 6 RCTs, consider the potential expansion in the use of EVT, outline the penultimate or next steps during the encore of this drama and ponder the broad implications of these recent findings on the entire stroke field for many years to come. This logical rationale and perspective form the basis of Establishing Neuroimaging Criteria of Revascularization Efficacy (ENCORE), the proposed pooled, subject-level, meta-analysis of the recent large core trials, leveraging imaging re-adjudication by a collaborative, imaging core lab with documented expertise. Expansion of the treatment indications for EVT will likely ensue, yet numerous questions persist regarding other confounding variables that we normally use in routine clinical practice. Precision medicine for large core ischemic stroke mandates a more detailed investigation of the numerous clinical, imaging and angiographic variables that each trial dataset collected. In a simple pooled meta-analysis, these varying definitions, methodology and analytic approaches preclude anything beyond current summary results showing that EVT is favored, in general, over medical treatment. The epilog of the large core trials can be written by ENCORE, using the imaging and statistical methods and relevant expertise of the prior Highly Effective Reperfusion Evaluated in Multiple Endovascular Stroke Trials (HERMES) collaboration.